Influence of Sedimentary Environment Evolution on Fingerprint Characteristics of Methane Isotopes: A Case Study From Hangzhou Bay. Issue 3 (20th March 2023) - Jiang, Wenqin; Cao, Ke; Duan, Xiaoyong; He, Xingliang; Yin, Ping; Chen, Junbing; Xie, Yongqing; Liu, Jun; Cao, Binhua; Yu, Xinyang; Dong, Hailiang; Hou, Weiguo
Abstract: To better understand the depositional constraints on the fingerprint characteristics of methane isotopes, we present a set of carbon/hydrogen isotopic data for CH4, CO2, pore water, carbonate, and total organic carbon along a 70‐m sedimentary core. The sedimentary facies (Units I, II, and III from upper to bottom) suggested depositional environments of the present estuary, shallow marine, and floodplain‐estuary. Calculations suggested that around 86% of methane was produced through the CO2 reduction pathway. In this pathway, the hydrogen in CH4 is from ambient water, while the carbon is from dissolved inorganic carbon. Correspondingly, our study showed that the values of δ DCH4 displayed similar trends with those of δDH2O and Cl − concentrations along the depth profiles. The low δDCH4 below 44.5 m corresponded to low δDH2O and low salinity during the cold and low‐sea‐level period. The values of δ 13 CCH4 generally synchronously changed with those of δ 13 CCO2 . The variation trends of δ 13 CCH4 and δ 13 CCO2 were the same with δ 13 Ccarbonate from 10 to 70 m depth but decoupled above 10 m. The values of δ 13 CCH4 in Units II and III were correlated with the δ 13 Ccarbonates, which is related to the sedimentary processes. But decoupling of low values of δ 13 CCH4 and δ 13 CCO2 from δ 13 Ccarbonates in Unit I may be related to preferential microbial consumption of labile compounds with light carbon isotopic compositions, such as lipids. In short, the variations of δ 13 CCH4 and δ DCH4 were largely related to the sedimentary process, which controlled the isotopic compositions of both water and carbonate. Plain Language Summary: As an important greenhouse gas, methane (CH4 ) contributes more to global warming than the same mole's carbon dioxide (CO2 ). The methane isotopic composition is widely used to trace sources. Coastal sediments, recording the rise and stabilization of the global sea level since the Last Glacial Maximum, host enormous volumes of CH4 . Of interest is whether the depositional process could impact methane isotopic signatures, adding uncertainty to the traceability. We conducted analyses including C/H isotopic data of CH4, CO2, porewater, carbonates, and total organic carbon along a 70‐m sedimentary core from Hangzhou Bay, China. Calculations suggested that about 86% of methane was produced through the CO2 reduction pathway. In this pathway, the hydrogen in CH4 is derived from ambient water, while the carbon is from CO2, which was isotopically in equilibrium with carbonate. Our results suggested that sedimentary processes are the primary abiotic factors affecting the variations of the stable carbon and hydrogen isotopic compositions of biogenic CH4 from coastal sediment. Key Points: Higher than 80% of biogenic methane along the sediment core was produced through the CO2 reduction pathway C and H of biogenic CH4 from ambient CO2 and H2 are isotopically in equilibrium with ambient carbonate and water, respectively The sedimentary process is one of the primary abiotic factors affecting the variations of δ 13 CCH4 and δDCH4 from coastal sediment